Optimalisasi pembelajaran berbasis kompetensi pada pendidikan kejuruan - Herminanto Sofyan (Jurnal Pendidikan Vokasi, 2011)
COMPETENCE-BASED LEARNING OPTIMIZATION IN VOCATIONAL EDUCATIONCompetency Based Learning needs changes in curriculum design from subject matter to competency. Teacher needs to be able to design learning of competency and to identify learner diversity. Learing process at educational unit is carried out in interactive, inspiring, enjoying, challenging, motivating manners for learners and provide enough space for students to be active, creative, and otonomous align with aptitudes and talents. Teachers generate student positive attitudes through learning activities in order to develop their seminal apttitudes. Optimazing of competency based learning could be achieved through experiential learning, learning material development, the use of learning resources and media.